A Framework and Research Agenda on Technological Capability in a Dynamic Market: A Bibliometric Review - Chebo, Abdella Kosa; Bulto, Tadesse Weyuma; Negasa, Semu Bacha; Dhliwayo, Shepherd (International Review of Management and Marketing, 2026)
Technological capability (TC) is crucial for firms operating in uncertain environments characterised by fierce rivalry, quick changes in the market, and technology. It entails utilizing technology to simplify the transformation of inputs into outputs, manage resources, and adapt to environmental changes—all of which support the potential success of businesses. However, there is no well-defined framework for TCs that fit a dynamic market. To address this, a bibliometric analysis and systematic review were used to create a framework for TC in a dynamic market that integrates TC's existing knowledge with new concepts. The framework shows how businesses' strategic orientations can direct them to build strong TCs that are interwoven with other capabilities like innovation capability, marketing capability, dynamic capability, absorptive capability, and so on, to ensure business success. The provision of comprehensive scientific knowledge about TC in the dynamic market is aided by the presentation of integrative findings on the conceptual relationship of TC with its numerous antecedents and consequences. Therefore, it is suggested that future researchers carry out more investigation and provide clarification on how TCs are linked with various organisational capabilities in a changing market environment. The potential of the above factors as moderators, mediators, or control variables should also be empirically tested. Furthermore, for businesses to derive greater benefit from sophisticated technologies, they must establish a solid knowledge base and possess the capacity to assimilate new information.